Phosphorous uptake rate in two low phosphorous updated species, Aspalathus linearis and Podalyria calyptrata - Basic, Dunja (Department of Biological Sciences, 2017)
Due to the low P nature of soils within the fynbos biome of the Cape Floristic Region, plants have developed numerous mechanisms which enable them to better acquire phosphorous. A number of species have been reported to have specialised root morphologies (root clusters, mycorrhizae) that enhance P uptake. Plants may also down-regulate the uptake of P by decreasing the expression of genes that encode P transporters. Two Fabaceae species, Podalyria calyptrata and Aspa/athus linearis, were grown in hydroponics for 5 months at a low P supply of 4μM and P-depletion studies were conducted thereafter at 5 levels of external P (4, 10, 20, 50 and lOOμM). Growth rates (biomass accumulation) were also calculated as were root to shoot ratios for both species. A. linearis had a higher uptake rate than P. calyptrata. While the fresh biomass growth rate was similar in both species, P. calyptrata had a higher dry weight root to shoot ratio than A. linearis. The results showed that both species exhibited a lack of response to increasing P concentrations and had similar RGRs. Their uptake rates differed significantly (p<0.05) and this was likely due to their different root:shoot ratios. This indicates that both species would effectively grow in low P soils and in the case of P. calyptrata, in high P soils as well.